Community case management of lower chest indrawing pneumonia with oral amoxicillin in children in Kenya. (20th December 2018) - Onono, Maricianah; Abdi, Mohammed; Mutai, Kennedy; Asadhi, Elijah; Nyamai, Rachel; Okoth, Peter; Qazi, Shamim Ahmad
Abstract: Aim: To determine the accuracy and effectiveness of community health workers (CHWs) when compared to trained nurses for management of pneumonia in Kenyan children. Methods: In Homabay County in western Kenya, children 2–59 months of age with lower chest indrawing pneumonia were identified, classified and treated by CHWs with oral amoxicillin (90 mg/kg per day) for five days at home. Trained nurses visited the child within 24 hours to verify diagnosis; and on day 4 and 14 to assess treatment outcomes. Results: CHWs identified 1906 children with lower chest indrawing pneumonia. There was an 88.7% concordance in classification and treatment for lower chest indrawing pneumonia by CHWs compared to nurses. Children with moderate malnutrition (OR 1.68; 95% CI: 1.22–2.30), comorbidities such as diarrhoea or malaria (OR 1.55; 95% CI: 1.32–1.81) or an additional day of delay in care seeking (OR 1.06; 95% CI: 1.02–1.10) were more likely to have an incorrect classification of lower chest indrawing by the CHW. Comorbidity (OR 1.66; 95% CI: 1.12–2.48) and fast breathing (OR 4.66; 95% CI: 1.26–17.27) were significantly associated with treatment failure on day 14. Conclusion: CHWs can correctly manage lower chest indrawing pneumonia even in high‐mortality settings, such as western Kenya, in sub‐Saharan Africa.